Organic management of soft rot of ginger (Zingiber officinale) in Sikkim Himalayan region - GOPI, R; KALITA, H; AVASTHE, R K (The Indian Journal of Agricultural Sciences, 2016)
Soft rot is one of the most important diseases of ginger (Zingiber officinale Rose.) in Sikkim. Experiment was conducted during 2011-12 and 2012-13 to study the effect of various organic treatments on the incidence of soft rot, germination and yield of ginger. In the survey the highest incidence of soft rot was observed in South district 30.0 and 25.7%, respectively, during 2011-12 and 2012-13, whereas lowest incidence of disease was observed in North district (10.0 and 9.7%, respectively). In the in vitro study, garlic @ 10% concentration was found to be the most effective in reducing the growth of the soft rot pathogen with 62.3% inhibition. Among the 10 selected Trichoderma isolates, Trichoderma harzianum collected from Todaybusty, South Sikkim was the most effective in reducing the Pythium aphanidermatum colony growth (72.0%). Among the treatments evaluated against the soft rot, the hot water treatment @ 47oC for 30 min + T. harzianum + three periodic drenching of COC @ 0.3 % at 20 day interval was found effective with the lowest average per cent incidence (16.7 and 15.0) followed by hot water treatment @ 47oC for 30 min + neem cake @ 2 tonnes/ha + COC 0.3%. The hot water treatment @ 47oC for 30 min + T. harzianum + COC @ 0.3%, recorded maximum germination (91.3 and 90.3%) and highest yield (158 and 126 q/ha).